Portuguese validation of the Emotion Regulation Questionnaire for Children and Adolescents (ERQ-CA): relations with self-esteem and life satisfaction - Teixeira, Ana (2015)
Despite the growing study of adolescents' emotion regulation (ER) and its importance for developmental trajectories, research has focused mainly on psychopathology by contrast with positive functioning. The lack of adequate age measures on emotion regulation has been also largely recognized. The present study aims to explore psychometric properties and construct validity of the Emotion Regulation Questionnaire for Children and Adolescents (ERQ-CA) (Gullone and Taffe, 2012) in a sample of 809 Portuguese adolescents. The Portuguese version (QRE-CA) showed adequate reliability and the Confirmatory Factorial Analysis presented a good fit confirming the two-factor model found by Gullone and Taffe (2012). Measurement invariance tests showed intergroup invariance for gender and school grade. Additionally, convergent validity showed positive associations between the reappraisal strategy and measures of positive psychological functioning (self-esteem and satisfaction with life). The suppression strategy presented negative associations with those same variables.Findings suggest that the QRE-CA is a valid and reliable measure for evaluating strategies of ER. Final considerations highlight the importance of extending research on adolescents' emotion regulation and positive functioning.